Characterization of polyamine metabolism predicts prognosis, immune profile, and therapeutic efficacy in lung adenocarcinoma patients - Li, Zhouhua; Wu, Yue; Yang, Weichang; Wang, Wenjun; Li, Jinbo; Huang, Xiaotian; Yang, Yanqiang; Zhang, Xinyi; Ye, Xiaoqun (Frontiers in Cell and Developmental Biology, 2024)
The polyamine modification patterns in lung adenocarcinoma (LUAD) and their impact on prognosis, immune infiltration, and anti-tumor efficacy have not been systematically explored.Patients from TCGA were classified into subtypes according to polyamine metabolism-related genes using the consensus clustering method, and the survival outcomes and immune profile were compared. Meanwhile, gene cluster was constructed according to DEGs from the subtypes. Subsequently, polyamine metabolism-related score (PMRS) system was established using Lasso-multivariate regression analysis in the TCGA training cohort (n=245), which can be applied to characterize prognosis. To verify the predicted performance of PMRS, the internal cohort (n=245) and the external cohort (n=244) were recruited. The relationship between PMRS and immune infiltration and antitumor response was investigated.Two distinct patterns (C1 and C2) were identified, in which the C1 subtype presented adverse prognosis, high CD8 + T cell infiltration, TMB, immune checkpoint, and low TIDE. Furthermore, two gene clusters were established and similar findings were observed. PMRS, including three genes (SMS, SMOX, PSMC6) was then constructed to characterize the polyamine metabolic patterns, and the patients were divided into high-and low-PMRS groups. As confirmed by the validation cohort, the high-PMRS group possessed poor prognosis. Moreover, external samples and immunohistochemistry confirmed that three genes were highly expressed in tumor samples. Finally, immunotherapy and chemotherapy may be beneficial to the high-PMRS group based on the immunotherapy cohorts and low IC50 value.We identified distinct polyamine modification patterns and established PMRS to provide new insights into the mechanism of polyamine action and improve the current anti-tumor strategy of LUAD.